2010
DOI: 10.1155/2010/698730
|View full text |Cite
|
Sign up to set email alerts
|

PPARs in the Renal Regulation of Systemic Blood Pressure

Abstract: Recent research has revealed roles for the peroxisome proliferator activated receptor (PPAR) family of transcription factors in blood pressure regulation, expanding the possible therapeutic use of PPAR ligands. PPARα and PPARγ modulate the renin-angiotensin-aldosterone system (RAAS), a major regulator of systemic blood pressure and interstitial fluid volume by transcriptional control of renin, angiotensinogen, angiotensin converting enzyme (ACE) and angiotensin II receptor 1 (AT-R1). Blockade of RAAS is an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 88 publications
(204 reference statements)
1
35
0
Order By: Relevance
“…343). Thus, enalapril upregulates PPAR-␣ and PPAR-␥ and displays antiatherogenic and anti-inflammatory effects in mice (90).…”
Section: The Sirtuin-ras Connectionmentioning
confidence: 99%
“…343). Thus, enalapril upregulates PPAR-␣ and PPAR-␥ and displays antiatherogenic and anti-inflammatory effects in mice (90).…”
Section: The Sirtuin-ras Connectionmentioning
confidence: 99%
“…PPAR agonists can attenuate the adverse effects of Ang II by downregulating Ang II concentration and ACE and AT1R gene expression [6]. This is the first study to verify the upregulation of ACE2 by PPAR agonists in all insulin-sensitive tissues.…”
Section: Discussionmentioning
confidence: 74%
“…HFD-induced elevation in FFA activates PPAR [19], which subsequently regulates RAS [6]. Additionally, the upregulation of hepatic ACE2 expression may result from the NASHrelated fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has a well-recognized role in regulating multiple metabolic processes. PPARγ can regulate BP by modulation of the renin angiotensin aldosterone system (RAAS), which is an important pathway in managing systemic BP and interstitial fluid volume (Roszer and Ricote, 2010). In transgenic and knockout mice studies with mutant PPARγ, it has been demonstrated that quantitative variants causing decreased PPARγ expression are potential contributors to EH (Halabi et al, 2008;Tsai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%